2015
DOI: 10.1037/a0039756
|View full text |Cite
|
Sign up to set email alerts
|

Can a gray seal (Halichoerus grypus) generalize call classes?

Abstract: Past researchers have found that gray seals (Halichoerus grypus) are capable of classifying vocal signals by call type using a trained set, but were unable to generalize to novel exemplars (Shapiro, Slater, & Janik, 2004). Given the importance of auditory categorization in communication, it would be surprising if the animals were unable to generalize acoustically similar calls into classes. Here, we trained a juvenile gray seal to discriminate novel calls into 2 classes, "growls" and "moans," by vocally matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Given the importance of auditory categorization in communication systems (Stansbury et al, 2015), and the anecdotal and experimental evidence of vocal imitation and plasticity in this species (Eaton, 1974;Murayama et al, 2014;Ridgway et al,1985), these results were unexpected. The following sections evaluate the various possible explanations for why this particular beluga showed difficulty mastering this vocal task.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Given the importance of auditory categorization in communication systems (Stansbury et al, 2015), and the anecdotal and experimental evidence of vocal imitation and plasticity in this species (Eaton, 1974;Murayama et al, 2014;Ridgway et al,1985), these results were unexpected. The following sections evaluate the various possible explanations for why this particular beluga showed difficulty mastering this vocal task.…”
Section: Discussionmentioning
confidence: 91%
“…Size of the training set. Stansbury et al (2015) argued convincingly that small training sets impact a subject's ability to generalize to novel stimuli. They re-created Shapiro et al's (2004) earlier categorical matching study on two grey seal pups, which were trained successfully to respond to playbacks of moans and $?!…”
Section: Experimental Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinnipeds are well known for their trainability in captivity and a number of studies have shown that they are capable of usage learning as demonstrated by conditioned production of calls in their repertoire [ 45 , 46 ]. Training studies on harbour seals ( Phoca vitulina ) [ 45 ] and walrus ( Odobenus rosmarus ) [ 47 ] have also shown that they can invent calls as judged by a trainer and increase the variability of their calls when rewarded accordingly.…”
Section: Pinnipedsmentioning
confidence: 99%
“…Like the deer wasting disease example, annual culling would be needed to maintain any population control. Second, gray seals are relatively intelligent animals as demonstrated by their capacity for vocal learning (Shapiro et al 2004, Stansbury et al 2015 and as such likely possess a level of threat awareness at least as high as a badger or a fox. The likelihood that widespread culling would be perceived as a threat by the seals is high, potentially causing them to move to other areas of Cape Cod and increasing the risk of human-shark encounters in those currently unaffected areas.…”
Section: Culling For Disease Controlmentioning
confidence: 99%